2021
DOI: 10.1007/s43452-021-00286-4
|View full text |Cite
|
Sign up to set email alerts
|

A multiscale experimental analysis of mechanical properties and deformation behavior of sintered copper–silicon carbide composites enhanced by high-pressure torsion

Abstract: Experiments were conducted to investigate, within the framework of a multiscale approach, the mechanical enhancement, deformation and damage behavior of copper–silicon carbide composites (Cu–SiC) fabricated by spark plasma sintering (SPS) and the combination of SPS with high-pressure torsion (HPT). The mechanical properties of the metal–matrix composites were determined at three different length scales corresponding to the macroscopic, micro- and nanoscale. Small punch testing was employed to evaluate the stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…In particular, the limitation of the possible grain growth due to the lower sintering temperature, higher heating rate, and shorter sintering time in comparison to other methods makes it more and more popular. [36,41,42] We modified the process conditions to observe the microstructure and phase evolution of the sintered material. It should be emphasized that the relative density of the material is comparable (except for Sample 5, sintered in lower pressure assistance), which was the goal of the experiments, but the structure is significantly different.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the limitation of the possible grain growth due to the lower sintering temperature, higher heating rate, and shorter sintering time in comparison to other methods makes it more and more popular. [36,41,42] We modified the process conditions to observe the microstructure and phase evolution of the sintered material. It should be emphasized that the relative density of the material is comparable (except for Sample 5, sintered in lower pressure assistance), which was the goal of the experiments, but the structure is significantly different.…”
Section: Discussionmentioning
confidence: 99%
“…Sintered copper-silicon carbide composite specimens were tested using the SPT method in. 9 No assessment of the yield and ultimate stress was provided but it was reported that the shape of the SPT force-displacement curve could be used as an indicator for a ductile, brittle or mixed mode of fracture. In 10 SPT was used to estimate the yield and ultimate stress of Al-4 vol%Al 4 C 3 composites following equal channel angular pressing.…”
Section: Introductionmentioning
confidence: 99%